2017
DOI: 10.1108/wjemsd-09-2016-0045
|View full text |Cite
|
Sign up to set email alerts
|

Institutions and entrepreneurship: the mediating role of corruption

Abstract: Purpose The purpose of this paper is to examine the mediating role of corruption in the relationship between entrepreneurship and institutional quality in a sample of 90 countries from all around the world. Design/methodology/approach The data were collected from the Global Entrepreneurship Monitor, which developed a model where Corruption Perception Index as a proxy for corruption mediates the relationship between the variable rule of law as a proxy for institutional quality and opportunity entrepreneurship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…It is likely that bankruptcy laws provide greater legal support for entrepreneurs in developing countries where informal institutions would otherwise regulate the insolvency (Estrin & Mickiewicz, 2011). Hypotheses H4a and H4b are supported (Fig.1H) by showing corruption acts as grease' than sand for the wheel of business (Méon & Weill, 2010), with the effect being stronger for developing countries (Mohammadi Khyareh, 2017). In developed countries with higher-quality institutions, corruption works as an additional tax (Belitski et al 2016) and has a negative impact on entry when the corruption is in its fourth quintile (>1.5 see Fig.1H).…”
Section: Table 2 About Here Figure 1 About Here Results and Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…It is likely that bankruptcy laws provide greater legal support for entrepreneurs in developing countries where informal institutions would otherwise regulate the insolvency (Estrin & Mickiewicz, 2011). Hypotheses H4a and H4b are supported (Fig.1H) by showing corruption acts as grease' than sand for the wheel of business (Méon & Weill, 2010), with the effect being stronger for developing countries (Mohammadi Khyareh, 2017). In developed countries with higher-quality institutions, corruption works as an additional tax (Belitski et al 2016) and has a negative impact on entry when the corruption is in its fourth quintile (>1.5 see Fig.1H).…”
Section: Table 2 About Here Figure 1 About Here Results and Discussionmentioning
confidence: 85%
“…We used measures available in the World Economic Forum (WEF Global Competitiveness Report), GEM and WIPO data over 2005-2015, drawing on principles of productive and unproductive entrepreneurial behavior (Baumol, 1990). We drew from the existing literature (Sobel, 2008;Mohammadi Khyareh, 2017) and created a net entrepreneurial productivity (NEP) index for 74 countries following Sobel's (2008) approach but using six new proxies. These proxies capture entrepreneurial behavior and the environment in a country which may affect the choice between productive and unproductive entrepreneurship (see Table A3 in online Appendix).…”
Section: Data and Methodology Data And Samplementioning
confidence: 99%
See 1 more Smart Citation
“…The average level of EE intensity is 4.72 with 1.57 standard deviation. Taken together our two measures represent a novel approach to measuring various aspects of EEs, building on Khyareh's (2017) recent quality of entrepreneurship review.…”
Section: Ee Intensitymentioning
confidence: 99%
“…A U-shaped relationship was found between political stability and entrepreneurship via corruption channel. The study by Khyareh (2017) revealed that institutional quality mediates the relationship between corruption and entrepreneurship in a panel of 90 economies. Rani and Kumar (2021) showed that institutional factors such as government effectiveness have considerable impact on entrepreneurial operations in BRICS economies.…”
Section: Theories Relevant Studies and Hypothesesmentioning
confidence: 99%